Children and parents' perspectives on the acceptability of three management strategies for dental caries in primary teeth within the 'Filling Children's Teeth: Indicated or Not' (FiCTION) randomised controlled trial - a qualitative study - Sarab El-Yousfi; Nicola P. T. Innes; Richard D. Holmes; Ruth Freeman; Kathryn B. Cunningham; Elaine McColl; Anne Maguire; Gail V. A. Douglas; Janet E. Clarkson; Zoe Marshman (BMC, 2020)
Abstract Background The Filling Children's Teeth: Indicated Or Not? (FiCTION) randomised controlled trial (RCT) aimed to explore the clinical- and cost-effectiveness of managing dental caries in children's primary teeth. The trial compared three management strategies: conventional caries management with best practice prevention (C + P), biological management with best practice prevention (B + P) and best practice prevention alone (PA)-based approaches. Recently, the concept of treatment acceptability has gained attention and attempts have been made to provide a conceptual definition, however this has mainly focused on adults. Recognising the importance of evaluating the acceptability of interventions in addition to their effectiveness, particularly for multi-component complex interventions, the trial design included a qualitative component. The aim of this component was to explore the acceptability of the three strategies from the perspectives of the child participants and their parents. Methods Qualitative exploration, based on the concept of acceptability. Participants were children already taking part in the FiCTION trial and their parents. Children were identified through purposive maximum variation sampling. The sample included children from the three management strategy arms who had been treated and followed up; median (IQR) follow-up was at 33.8 (23.8, 36.7) months. Semi-structured interviews with thirteen child-parent dyads. Interviews were transcribed verbatim and analysed using a framework approach. Results Data saturation was reached after thirteen interviews. Each child-parent dyad took part in one interview together. The participants were eight girls and five boys aged 5-11 years and their parents. The children's distribution across the trial arms was: C + P n = 4; B + P n = 5; PA n = 4. Three key factors influenced the acceptability of caries management in primary teeth to children and parents: i) experiences of specific procedures within management strategies; ii) experiences of anticipatory dental anxiety and; iii) perceptions of effectiveness (particularly whether pain was reduced). These factors were underpinned by a fourth key factor: the notion of trust in the dental professionals - this was pervasive across all arms. Conclusions Overall children and parents found each of the three strategies for the management of dental caries in primary teeth acceptable, with trust in the dental professional playing an important role.